Supplemental Porang Glucomannan Flour (Amorphophallus muelleri Blume) on Green Grass Jelly (Cyclea barbata L. Miers) Texture, Syneresis, and Moisture Content - Chandra Wira Aryawan; Ika Fitriana (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2022)
This study aims to determine the effect of adding porang glucomannan flour as a hydrocolloid on the texture, syneresis, and moisture content of green grass jelly gel (Cyclea barbata L. Miers). This research was conducted at Food & Agricultural Products Engineering Laboratory, and Chemistry & Biochemistry Laboratory of Semarang University in August 2022. Research experimental design that is used is one factor with completely randomized design and 4 replications. The treatment was adding porang glucomannan flour in a solution of green grass jelly extract consisting of: P0 = 0%, P1 = 0.5%, P2 = 1%, P3 = 1.5%, and P4 = 2% (percentage of porang flour in the solution of green grass jelly extract (w/v)). The observed parameters are texture, syneresis and moisture content. If there is a significant difference among the treatments, it will be tested with DMRT (Duncan Multiple Range Test). Based on the results of the study, it can be concluded that the addition of porang flour had a significant effect on the green grass jelly gel. In the texture aspect, the trend of increasing gel strength expressed in bloom load (g) in each treatment ranged from P0 = 6.63 gf to P4 = 31.13 gf, decreasing syneresis trend ranged from P0 = 38.35% to P4 = 0.0745%, and moisture content decreasing trend starting from P0 = 89.15% to P4 = 72.59% as the concentration of porang flour was added.